Pistachios for Health: What Do We Know About This Multifaceted Nut? - Hernández-Alonso, Pablo (Nutr Today, 2016)
Human beings have known about pistachio nuts since 6000 bc. Since then, pistachios have been systematically incorporated into the diet of various cultures. They are nutrient-dense nuts with a healthy nutritional profile that contains fiber, unsaturated fatty acids and antioxidant compounds.